2009
DOI: 10.1073/pnas.0812817106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cacao use in the Prehispanic American Southwest

Abstract: archaeology ͉ Chaco Canyon ͉ ritual ͉ chemistry ͉ organic residues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 6 publications
0
79
1
Order By: Relevance
“…However, previous research has indicated use of cacao drinks in a number of contexts in this area (1,2,17). No study has argued previously for the presence of I. vomitoria in the US Southwest and Mexican Northwest, but we believe our results suggest that many samples contained residues from drinks based on high-caffeine holly rather than low-caffeine cacao.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…However, previous research has indicated use of cacao drinks in a number of contexts in this area (1,2,17). No study has argued previously for the presence of I. vomitoria in the US Southwest and Mexican Northwest, but we believe our results suggest that many samples contained residues from drinks based on high-caffeine holly rather than low-caffeine cacao.…”
Section: Discussioncontrasting
confidence: 38%
“…The results have implications for economic and social relations among North American populations. T he discovery of cacao residues in ceramics from Pueblo Bonito, Chaco Canyon, New Mexico, demonstrated exchange with populations in the tropical areas where Theobroma cacao grew in the past as well as consumption of ritual drinks by at least A.D. 1000 in the canyon (1,2). It also raised questions about the time depth and geographic extent of this exchange in the US Southwest and Mexican Northwest.…”
mentioning
confidence: 99%
“…Although Chacoan exchange networks extended as far as Mesoamerica for prestige items (34,35), the procurement of basic, labor-intensive resources from multiple distant landscapes, with shifting dynamics of use, is a prominent feature of Chacoan society. Testing for similar patterns at other pre-Columbian and historic sites in North America would be a fruitful endeavor and is possible now because of a dense network of long tree-ring chronologies and the rich collection of archaeological wood material housed at the University of Arizona and National Park Service archives.…”
Section: Resultsmentioning
confidence: 99%
“…Recent analysis of residues in the fragments of these vessels recovered from the Bonito trash mounds revealed that at least some of the vessels contained residues of cacao, suggesting that Chacoans drank a type of chocolate beverage (39). Such beverages were an important component of Mesoamerican rituals.…”
Section: Microcosm: Great-house Burial Complexmentioning
confidence: 99%